The “memory wars” in divided societies: the case of Spain - I. L. Prokhorenko (Ибероамериканские тетради)
The author, using the identity approach and discourse analysis explores a serious political conflict in today’s Spain about historical memory, threatening solidarity and civilian identity of the Spaniards and also political stability in the society, divided on a variety of characteristics – economic, social, territorial, cultural, value, ethnic, linguistic, etc., which have acquired or are acquiring a political dimension. The alternative politics of memory, which are declared and carried out by different competing actors of political process at the country level, first of all being government and opposition parties, are analyzed in the article. The expression of authorities’ discourse of the present left coalition government on the issues of Spanish past in the country’s mediasphere is considered to understand the extent and depth of public and political debate on key problems of Spanish history and memory. The author uses a historical metaphor of conflict of the “two Spains” to assess “memory wars” in Spanish society, multicultural and divided on various grounds, identifying short-term (with a view of forthcoming general parliamentary elections, which will take place in 2022) and long-term strategic risks for inclusive nation-building and sustainable development of the country. A conclusion is made that a division based on party ideological principles is axial (dominant) in “memory wars”, despite the remaining sharpness of the vertical conflict between center and some particularist regions (primarily Catalonia); within the frame of this conflict there are attempts to reassess, anonymize, and get a hold of or mythologize various historic events and personas. Nowadays the dispute between “rightists” and “leftists” in assessment of Second Spanish Republic, number of victims on both sides during the civil war, Francoist regime, success of democratic transition in post-Francoist period and other “difficult” questions across Spanish past becomes more emotionally charged, deep and aggressive.